High-impermeability geomembrane and preparation method thereof
By combining modified mica sheets and zinc oxide with polymers, a high-permeability geomembrane was prepared, which solved the problems of insufficient puncture resistance and impermeability of geomembranes, improved the mechanical properties and impermeability of geomembranes, and extended their service life.
Patent Information
- Application Number
- CN202411415452.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-01-07
AI Technical Summary
Existing geomembranes are insufficient in terms of puncture resistance and seepage prevention, and are prone to aging, have poor low-temperature brittleness, and have a short service life.
Modified mica sheets and modified zinc oxide are combined with materials such as polyethylene and ethylene-vinyl acetate copolymer. The substrate layer and the rough surface layer are prepared by melt extrusion and spinning processes to form a highly impermeable geomembrane, which improves the compatibility and adhesion of the materials and enhances the mechanical properties and impermeability of the geomembrane.
It improves the tensile strength, impact strength and thermal stability of geomembranes, enhances their seepage prevention and flame retardant properties, extends their service life, reduces construction noise, and expands their application range.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and particularly relates to a high-impermeability geomembrane and a preparation method thereof. Background Art
[0002] Geomembrane is a new type of engineering material with high physical and mechanical properties such as tensile strength, tear resistance and bursting resistance. The product has the characteristics of high strength, good elongation, large deformation modulus, acid and alkali resistance, corrosion resistance, aging resistance, and good anti-seepage performance. It is suitable for anti-seepage, isolation, reinforcement, anti-cracking reinforcement, and protection involved in the construction of water conservancy, municipal engineering, construction, transportation, subways, tunnels, and railway projects. It is widely used in the anti-seepage treatment of dams and drainage ditches, as well as the anti-pollution treatment of waste yards.
[0003] At present, with the enhancement of comprehensive national strength, the construction standards and requirements of railways, highways, subways and municipal engineering in my country are gradually improving, and higher requirements are also put forward for the performance indicators of geomembrane materials. At the same time, the number of projects with special environments and special requirements is gradually increasing, and higher requirements are put forward for the strength and puncture resistance of geomembranes. However, geomembrane is a flexible material of polymer compounds with a thin thickness, so it is easy to break. It is easy to be damaged during transportation or construction, punctured by sharp objects such as stones, and ruptured due to excessive deformation or uneven settlement of the dam. The existing geomembranes also have the following defects: 1) The puncture resistance and anti-seepage performance cannot be improved at the same time; 2) The environmental stress cracking resistance is poor and the low temperature brittleness resistance is poor; 3) It is easy to age and has a short service life. Therefore, it is necessary to provide a geomembrane with high strength, anti-cracking protection, better puncture resistance and durability, and more convenient construction to address the shortcomings of the existing geomembranes, such as low strength and puncture resistance, easy aging, and poor low temperature brittleness resistance. Summary of the invention
[0004] The object of the present invention is to provide a high-impermeability geomembrane and a preparation method thereof, so as to solve the problem of low strength and puncture resistance of the geomembrane.
[0005] The purpose of the present invention can be achieved through the following technical solutions: A high-impermeability geomembrane comprises a substrate layer and a rough surface layer, wherein the substrate layer comprises the following raw materials in parts by weight: 45-60 parts of polyethylene, 15-20 parts of ethylene-vinyl acetate copolymer (EVA), 10-30 parts of carbon black masterbatch, 10-15 parts of modified mica flakes, 0.5-2 parts of antioxidant, 0.5-3 parts of dispersant; The modified mica sheet is prepared by the following steps: Add mica flakes to deionized water, heat to 60-70°C and stir for 8-12 hours, adjust the pH to 5-6, add lanthanum chloride solution, continue stirring and reacting for 2-3 hours, adjust the pH to 8-9, add anionic surfactant, stir, centrifuge and wash, vacuum dry to constant weight, grind and sieve to obtain modified mica flakes. In the above technical scheme, lanthanum ions and anionic surfactants are used to organically modify mica flakes, and lanthanum ions are intercalated into mica flake layers to undergo cation exchange reactions to obtain lanthanum-based mica flakes. The lanthanum ions between the layers not only combine with carboxylates, sulfonates and negative charges on the mica sheets to form ionic bonds, but also combine with carboxylates and sulfonates to form lanthanum carboxylates and lanthanum sulfonates. At this time, the lanthanum carboxylates and lanthanum sulfonates interact with the mica sheets in the solution through electrostatic attraction and are adsorbed on the surface of the mica sheets, forming chemical adsorption and physical adsorption. A layer of organic matter is covered between and on the surface of the mica sheets. The interlayer spacing of the organically modified mica sheets is increased, and the hydrophobic property is improved, which greatly improves the surface activity of the mica sheets and the compatibility with the base material, improves the dispersibility of the mica sheets in the base material, and can also strengthen the adhesion between the mica sheets and the substrate.
[0006] Furthermore, the anionic surfactant is one of sodium dodecyl sulfonate and sodium dodecyl carboxylate.
[0007] Furthermore, the usage ratio of mica flakes, deionized water, lanthanum chloride solution and anionic surfactant is 1 g:50 mL:0.025-0.03 mL:0.1-0.15 g.
[0008] Furthermore, the mesh size of the sieving is 300-400 meshes.
[0009] Furthermore, the antioxidant is at least one of antioxidant 1010 , antioxidant 1076 , antioxidant 168 and antioxidant 626 .
[0010] Furthermore, the dispersant includes at least one of paraffin, EBS, polyethylene wax and magnesium stearate.
[0011] Furthermore, the rough surface layer is made of a composite material, and the composite material includes the following raw materials in parts by weight: 30-50 parts of low-density polyethylene, 15-20 parts of polycarbonate, 5-10 parts of polypropylene, 10-30 parts of modified zinc oxide, 0.5-1 part of zinc stearate, and 3-5 parts of azobisisobutyronitrile.
[0012] Furthermore, the modified zinc oxide is prepared by the following steps: Add nano zinc oxide and anhydrous ethanol to deionized water, perform ultrasonic treatment, add monohydrated citric acid, adjust the pH to 7-8, heat to 35-40°C, stir, wash, centrifuge, and vacuum dry to obtain modified zinc oxide. In the above technical solution, monohydrated citric acid with three carboxyl structures is used to esterify the hydroxyl groups on the surface of nano zinc oxide to generate ester bonds, which effectively improves the compatibility of nano zinc oxide with the base material, making it evenly dispersed in the base material and not easy to agglomerate.
[0013] Furthermore, the dosage ratio of nano zinc oxide, anhydrous ethanol, deionized water and citric acid monohydrate is 1 g: 10 mL: 50 mL: 0.3-0.5 g.
[0014] Furthermore, the particle size of the nano zinc oxide is 300-500nm.
[0015] The present invention also provides a method for preparing a high-impermeability geomembrane, comprising the following steps: Step 1, adding polyethylene, ethylene-vinyl acetate copolymer, carbon black masterbatch, modified mica flakes, antioxidant and dispersant into a mixer by weight to obtain a premix; melt blending low-density polyethylene, polycarbonate, polypropylene, modified zinc oxide, zinc stearate and azobisisobutyronitrile, extruding and granulating to obtain a composite material; Step 2, adding the premix to a melt extrusion device for melt blending, extrusion granulation, blow molding or calendaring to obtain a substrate layer; Step 3: spray the composite material onto at least one surface of the substrate layer obtained in step 2 by a spinning process to form a rough surface layer, and cool the layer to obtain a geomembrane.
[0016] Beneficial effects of the present invention: The invention provides a high-impermeability geomembrane and a preparation method thereof, comprising a substrate layer and a rough surface layer, wherein the substrate layer is prepared by melt extrusion and compression molding of polyethylene, EVA, carbon black masterbatch, modified mica flakes and other additives, and then a composite material is sprayed on at least one surface thereof by a spinning process to obtain a rough surface layer, and finally a geomembrane having advantages such as good mechanical properties and high temperature resistance is obtained. The modified mica flakes are added, blended with polyethylene, EVA, carbon black masterbatch, antioxidant and dispersant, and staggeredly distributed in the base material in a layered structure, effectively improving and enhancing the tensile strength, impact strength and thermal stability of the geomembrane. At the same time, the barrier and moisture resistance of the geomembrane are improved, thereby improving the anti-seepage performance of the geomembrane, and also enhancing the flame retardant and anti-ultraviolet performance of the geomembrane, slowing down the aging of the geomembrane and extending the service life. Adding EVA as a compatibilizer in the raw material not only improves the compatibility with the substrate, but also further improves the dispersibility of the modified mica flakes, which is conducive to enhancing the mechanical properties of the substrate layer. The high-impermeability geomembrane obtained by the invention has the advantages of good mechanical properties, weather resistance, high temperature resistance and durability, and the preparation method is environmentally friendly, energy-saving and time-saving.
[0017] The invention uses low-density polyethylene, polycarbonate and polypropylene as a matrix, nano zinc oxide and zinc stearate as fillers, and azobisisobutyronitrile as a foaming agent, and obtains a composite material through melt mixing. Finally, the composite material is sprayed on the surface of a substrate layer through a spinning process to form a rough surface, thereby enhancing the surface roughness and anti-slip performance of the geomembrane, improving the friction and firmness with the contact surface, and the rough part of the surface does not fall off after spinning, the roughening is long-lasting, and shock absorption and noise reduction are achieved, thereby effectively reducing noise pollution during construction and expanding the application range of the geomembrane. DETAILED DESCRIPTION
[0018] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0019] Example 1 This embodiment provides a modified mica sheet, and the preparation steps are as follows: Add 1g of mica flakes to 50mL of deionized water, heat to 60℃ and stir for 8h, adjust the pH to 5, add 0.025mL of lanthanum chloride solution (concentration 0.4mol / L), continue stirring and reacting for 2h, adjust the pH to 8, add 0.1g of sodium dodecyl sulfate, stir for 2h, centrifuge, and wash with hot deionized water until no Cl is detected in AgNO3. -, then washed with anhydrous ethanol three times, placed in a 70°C vacuum drying oven to dry to constant weight, ground through a 300-mesh sieve to obtain modified mica flakes.
[0020] Example 2 This embodiment provides a modified mica sheet, and the preparation steps are as follows: Add 1g of mica flakes to 50mL of deionized water, heat to 60℃ and stir for 8h, adjust the pH to 5, add 0.03mL of lanthanum chloride solution (concentration 0.4mol / L), continue stirring and reacting for 2h, adjust the pH to 8, add 0.15g of sodium dodecyl sulfate, stir for 3h, centrifuge, and wash with hot deionized water until no Cl is detected in AgNO3. - , then washed with anhydrous ethanol three times, placed in a 70°C vacuum drying oven to dry to constant weight, ground through a 350-mesh sieve to obtain modified mica flakes.
[0021] Example 3 This embodiment provides a modified mica sheet, and the preparation steps are as follows: Add 1g of mica flakes to 50mL of deionized water, heat to 60-70℃ and stir for 8-12h, adjust the pH to 6, add 0.025mL of lanthanum chloride solution (concentration is 0.4mol / L), continue stirring and reacting for 2-3h, adjust the pH to 9, add 0.12g of sodium dodecyl carboxylate, stir for 3h, centrifuge, and wash with hot deionized water until no Cl is detected in AgNO3. - , then washed with anhydrous ethanol three times, placed in a 70°C vacuum drying oven to dry to constant weight, ground through a 400-mesh sieve to obtain modified mica flakes.
[0022] Comparative Example 1 This comparative example provides a modified mica sheet, and the preparation steps are as follows: 1 g of mica flakes were added into 50 mL of deionized water, heated to 60° C. and stirred for 8 h, centrifuged, washed, dried in a vacuum drying oven at 70° C. to constant weight, and ground through a 300-mesh sieve to obtain modified mica flakes.
[0023] Example 4 This embodiment provides a modified zinc oxide, and the preparation steps are as follows: Add 1 g of nano zinc oxide (400 nm) and 10 mL of anhydrous ethanol to 50 mL of deionized water, ultrasonically treat for 1 h, add 0.35 g of citric acid monohydrate, adjust the pH to 7.5, heat to 35 ° C, stir continuously for 3.5 h, wash with anhydrous ethanol 3 times, centrifuge, and dry in a vacuum drying oven at 60 ° C for 24 h to obtain modified zinc oxide.
[0024] Example 5 This embodiment provides a modified zinc oxide, and the preparation steps are as follows: Add 1 g of nano zinc oxide (400 nm) and 10 mL of anhydrous ethanol to 50 mL of deionized water, ultrasonically treat for 1 h, add 0.45 g of citric acid monohydrate, adjust the pH to 7, heat to 35 ° C, stir continuously for 4 h, wash with anhydrous ethanol, centrifuge, and dry in a vacuum drying oven at 60 ° C for 22 h to obtain modified zinc oxide.
[0025] Comparative Example 2 This comparative example provides a modified zinc oxide, and the preparation steps are as follows:
[0026] 1 g of nano zinc oxide (400 nm) and 10 mL of anhydrous ethanol were added to 50 mL of deionized water, ultrasonically treated for 1 h, washed with anhydrous ethanol for 3 times, centrifuged, and dried in a vacuum drying oven at 60° C. for 24 h to obtain modified zinc oxide.
[0027] Example 6 This embodiment provides a high-impermeability geomembrane and a preparation method thereof: The preparation method comprises the following steps: Step 1, by weight, adding 50 parts of polyethylene, 15 parts of ethylene-vinyl acetate copolymer, 20 parts of carbon black masterbatch, 10 parts of modified mica flakes in Example 1, 0.5 parts of antioxidant 1010 and 0.5 parts of paraffin into a mixer for mixing to obtain a premix; melt blending 40 parts of low-density polyethylene, 15 parts of polycarbonate, 5 parts of polypropylene, 10 parts of modified zinc oxide in Example 4, 0.5 parts of zinc stearate and 3 parts of azobisisobutyronitrile, extruding and granulating to obtain a composite material; Step 2, adding the premix to a melt extrusion device for melt blending, extrusion granulation, blow molding or calendaring to obtain a substrate layer; Step 3: spray the composite material onto one surface of the substrate layer obtained in step 2 by a spinning process to form a rough surface layer, and cool it to obtain a geomembrane (the thickness of the geomembrane is 2 mm, and the surface spraying rate is 5%).
[0028] The high-impermeability geomembrane is prepared by the above steps.
[0029] Example 7 The only difference from Example 6 is that the modified mica sheet in Example 1 is replaced by the modified mica sheet in Example 3, and the amount used remains unchanged; the remaining steps are the same as Example 6.
[0030] Example 8 The only difference from Example 6 is that 10 parts of the modified mica sheets in Example 1 are replaced by 13 parts of the modified mica sheets in Example 1; the remaining steps are the same as those in Example 6.
[0031] Example 9 The only difference from Example 6 is that 10 parts of the modified zinc oxide in Example 4 are replaced by 25 parts of the modified zinc oxide in Example 5; the remaining steps are the same as Example 6.
[0032] Example 10 The only difference from Example 6 is that: Step 1, by weight, 55 parts of polyethylene, 18 parts of ethylene-vinyl acetate copolymer, 25 parts of carbon black masterbatch, 13 parts of modified mica flakes in Example 1, 0.5 parts of antioxidant 1010 and 0.5 parts of paraffin are added into a mixing machine for mixing to obtain a premix; 40 parts of low-density polyethylene, 15 parts of polycarbonate, 5 parts of polypropylene, 10 parts of modified zinc oxide in Example 4, 0.5 parts of zinc stearate and 3 parts of azobisisobutyronitrile are melt-blended, extruded and granulated to obtain a composite material; the remaining steps are the same as in Example 6.
[0033] Embodiment 11 The only difference from Example 10 is: Step 1, by weight, 55 parts of polyethylene, 18 parts of ethylene-vinyl acetate copolymer, 25 parts of carbon black masterbatch, 13 parts of modified mica flakes in Example 1, 0.5 parts of antioxidant 1010 and 0.5 parts of paraffin are added into a mixing machine for mixing to obtain a premix; 45 parts of low-density polyethylene, 18 parts of polycarbonate, 8 parts of polypropylene, 22 parts of modified zinc oxide in Example 4, 0.5 parts of zinc stearate and 4 parts of azobisisobutyronitrile are melt-blended, extruded and granulated to obtain a composite material; the remaining steps are the same as in Example 10.
[0034] Comparative Example 3 Compared with Example 6, the modified mica sheet in Example 1 is replaced by the modified mica sheet in Comparative Example 1, and the amount used remains unchanged; the remaining steps are the same as in Example 6.
[0035] Comparative Example 4 Compared with Example 6, 10 parts of the modified mica sheets in Example 1 are replaced by 7 parts of the modified mica sheets in Example 1; the remaining steps are the same as those in Example 6.
[0036] Comparative Example 5 Compared with Example 8, 13 parts of the modified mica sheets in Example 1 are replaced by 18 parts of the modified mica sheets in Example 1; the remaining steps are the same as those in Example 8.
[0037] Comparative Example 6 Compared with Example 6, the modified zinc oxide in Example 4 is replaced by the modified zinc oxide in Comparative Example 1, and the amount used remains unchanged; the remaining steps are the same as in Example 6.
[0038] Comparative Example 7 Compared with Example 6, 10 parts of the modified zinc oxide in Example 4 were replaced by 5 parts of the modified zinc oxide in Example 4; the remaining steps were the same as in Example 6.
[0039] Comparative Example 8 Compared with Example 9, 25 parts of the modified zinc oxide in Example 5 were replaced by 35 parts of the modified zinc oxide in Example 5; the remaining steps were the same as those in Example 6.
[0040] Comparative Example 9 Compared with Example 6, the only difference is: Step 1, by weight, 35 parts of polyethylene, 12 parts of ethylene-vinyl acetate copolymer, 5 parts of carbon black masterbatch, 10 parts of modified mica flakes in Example 1, 0.5 parts of antioxidant 1010 and 0.5 parts of paraffin are added into a banbury mixer for mixing to obtain a premix; 40 parts of low-density polyethylene, 15 parts of polycarbonate, 5 parts of polypropylene, 10 parts of modified zinc oxide in Example 4, 0.5 parts of zinc stearate and 3 parts of azobisisobutyronitrile are melt-blended, extruded and granulated to obtain a composite material; The performance tests were performed on the geomembranes obtained in Examples 6-11 and Comparative Examples 3-9: 1) Tensile yield strength and tensile breaking strength test: According to GB / T 17643-2011, the geomembrane standard test is carried out, and the testing instrument is the Z020 tensile testing machine of the German Zwick company.
[0041] 2) Puncture strength test: The geomembrane is tested according to the standard of CJ / T 234-2006.
[0042] 3) Right-angle tear strength: The geomembrane is tested according to the standard of CJ / T 234-2006.
[0043] 4) Resistance to environmental stress cracking: Tested according to GB / T17643-2011 standard, the testing instrument is HBS-1200 constant temperature water tank produced by Tokyo Rikkigi Co., Ltd.
[0044] 5) Friction test: The friction coefficient of geomembrane is measured using a pendulum friction coefficient tester with a sliding speed of 10 km / h.
[0045] The above test results are shown in Table 1: .
[0046] It can be seen from Table 1 that the high anti-seepage geomembrane prepared by the present invention has a tensile yield strength of more than 32.5 N / mm, a tensile breaking strength of more than 61.6 N / mm, a puncture strength of more than 534 N, a right-angle tear strength of more than 248 N, an environmental stress cracking resistance time of more than 374 h, a friction coefficient of more than 0.66, and a water vapor permeability coefficient of less than 0.32 × 10-13 It can be seen that the high anti-seepage geomembrane provided by the present invention has the characteristics of excellent mechanical properties, puncture strength, friction performance and high anti-seepage performance.
[0047] By comparing Comparative Example 3 with Example 6, it can be seen that the modified mica sheet in Comparative Example 1 is added in Comparative Example 3, and the modified mica sheet in Example 1 is added in Example 6. The mechanical properties of the geomembrane of Example 6 are higher than those of Comparative Example 3, and the water vapor permeability coefficient is lower than that of Comparative Example 3. It can be seen that the use of modified mica sheets after organic modification can improve the compatibility of the mica sheets with the sheath material, thereby improving the mechanical properties and barrier properties of the substrate layer, and further improving the puncture resistance and anti-seepage properties of the geomembrane.
[0048] By comparing Comparative Example 4 with Example 6, and Comparative Example 5 with Example 8, it can be seen that there are 7 parts of modified mica sheets in Comparative Example 4, 10 parts of modified mica sheets in Example 6, 18 parts of modified mica sheets in Comparative Example 5, and 13 parts of modified mica sheets in Example 8. The tensile yield strength, tensile breaking strength and other mechanical properties in Examples 6 and 8 are higher than those in Comparative Examples 4-5, and the water vapor permeability coefficient is lower than that in Comparative Examples 4-5, indicating that the amount of modified mica sheets will also affect the mechanical properties and anti-seepage properties of the geomembrane.
[0049] Comparison between Comparative Example 6 and Example 6 shows that the modified zinc oxide in Example 1 is added in Comparative Example 6, and the modified zinc oxide in Example 4 is added in Example 6. The friction coefficient and mechanical properties of the geomembrane obtained in Example 6 are higher than those in Comparative Example 6. It can be seen that the use of modified zinc oxide modified by citric acid monohydrate can improve the compatibility of zinc oxide with the base material, thereby improving the friction and mechanical properties of the rough surface layer. Comparison between Comparative Example 7 and Example 6, and between Comparative Example 8 and Example 9 shows that the amount of modified zinc oxide will also affect the mechanical properties and anti-seepage properties of the geomembrane.
[0050] By comparing Comparative Example 9 with Examples 10-11, it can be seen that the selection and dosage of the raw materials for the substrate layer and the rough surface layer will have a certain influence on the mechanical properties, friction properties, impermeability, etc. of the prepared geomembrane.
[0051] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0052] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A high-impermeability geomembrane, comprising a substrate layer and a rough surface layer, characterized in that: The substrate layer comprises the following raw materials in parts by weight: 45-60 parts of polyethylene, 15-20 parts of ethylene-vinyl acetate copolymer, 10-30 parts of carbon black masterbatch, 10-15 parts of modified mica flakes, 0.5-2 parts of antioxidant, and 0.5-3 parts of dispersant; The modified mica sheet is prepared by the following steps: Add mica flakes into deionized water, heat to 60-70°C and stir for 8-12 hours, adjust the pH to 5-6, add lanthanum chloride solution, continue stirring and reacting for 2-3 hours, adjust the pH to 8-9, add anionic surfactant, stir, centrifuge and wash, vacuum dry to constant weight, grind and sieve to obtain modified mica flakes.
2. A high-impermeability geomembrane according to claim 1, characterized in that: The anionic surfactant is one of sodium dodecyl sulfonate and sodium dodecyl carboxylate.
3. A high impermeability geomembrane according to claim 1, characterized in that: The dosage ratio of mica flakes, deionized water, lanthanum chloride solution and anionic surfactant is 1g:50mL:0.025-0.03mL:0.1-0.15g.
4. The high-impermeability geomembrane according to claim 1, characterized in that: The mesh size of the sieving is 300-400 meshes.
5. The high-impermeability geomembrane according to claim 1, characterized in that: The antioxidant is at least one of antioxidant 1010 , antioxidant 1076 , antioxidant 168 and antioxidant 626 .
6. The high-impermeability geomembrane according to claim 1, characterized in that: The dispersant includes at least one of paraffin wax, EBS, polyethylene wax and magnesium stearate.
7. The high-impermeability geomembrane according to claim 1, characterized in that: The rough surface layer is made of a composite material, and the composite material includes the following raw materials in parts by weight: 30-50 parts of low-density polyethylene, 15-20 parts of polycarbonate, 5-10 parts of polypropylene, 10-30 parts of modified zinc oxide, 0.5-1 part of zinc stearate, and 3-5 parts of azobisisobutyronitrile.
8. The high-impermeability geomembrane according to claim 1, characterized in that: The modified zinc oxide is prepared by the following steps: Add nano zinc oxide and anhydrous ethanol into deionized water, perform ultrasonic treatment, add monohydrated citric acid, adjust the pH value to 7-8, heat to 35-40° C., stir, wash, centrifuge, and vacuum dry to obtain modified zinc oxide.
9. The high-impermeability geomembrane according to claim 8, characterized in that: The dosage ratio of nano zinc oxide, anhydrous ethanol, deionized water and monohydrated citric acid is 1g:10mL:50mL:0.3-0.5g.
10. The method for preparing a high-impermeability geomembrane according to claim 1, characterized in that: The following steps are involved: Step 1, adding polyethylene, ethylene-vinyl acetate copolymer, carbon black masterbatch, modified mica flakes, antioxidant and dispersant into a mixer by weight to obtain a premix; melt blending low-density polyethylene, polycarbonate, polypropylene, modified zinc oxide, zinc stearate and azobisisobutyronitrile, extruding and granulating to obtain a composite material; Step 2, adding the premix to a melt extrusion device for melt blending, extrusion granulation, blow molding or calendaring to obtain a substrate layer; Step 3: spray the composite material onto at least one surface of the substrate layer obtained in step 2 by a spinning process to form a rough surface layer, and cool the layer to obtain a geomembrane.
Citation Information
Cited By
Composite plastic for geotechnical cloth and preparation method thereof
CN120137300A